Analisis Kesulitan Belajar Matematika Pada Soal Hots Materi Bilangan Bulat Siswa Kelas IV SDN 1 Gunungsari - Rizky Nuras Pratama; Ervina Eka Subekti; M. Yusuf Setia Wardana (Universitas PGRI Adi Buana Surabaya, 2021)
The background of this research is the low mathematics score of HOTS questions in integer material for the fourth grade students of SDN 1 Gunungsari. The problem in this research is how the difficulties found in solving HOTS questions on integer material in grade IV SD N 1 Gunungsari? The objective that can be achieved in this study is to describe the difficulties of students in solving HOTS questions in integer material in grade IV SDN 1 Gunungsari. This type of research is qualitative research. Qualitative research, which describes the data obtained in the field. The research design used is also a qualitative descriptive study. The results of this study were the students' learning difficulties in solving HOTS questions in integer material were students having difficulty understanding what was being asked in the questions properly so that students had difficulty applying the right formula to solve the problem correctly. Students are also less careful in working on the questions so that the answers obtained are not optimal.